2003
DOI: 10.1097/00130404-200307000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the R2 Subunit of Ribonucleotide Reductase in Human Nasopharyngeal Cancer Cells Reduces Radiosensitivity

Abstract: An increase in R2 protein levels and RR activity in KB/M2 cells results in IR resistance, which appears mediated by enhanced IR damage repair during G2. R1 protein overexpression in these isogenic human tumor cells (KB/M1) did not affect RR activity or IR response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…It has been shown that an increase in RRM2 protein levels and RR activity in human nasopharyngeal cancer cells results in ionizing radiation resistance, which appears mediated by enhanced ionizing radiation damage repair during G2 phase of the cell cycle. However, overexpression of the large subunit, RRM1, of RR in these cells did not affect RR activity or ionizing radiation response (Kuo et al, 2003). RRM2 overexpression is also associated with gemcitabine chemoresistance in pancreatic adenocarcinoma cells, and that suppression of RRM2 expression using RNA interference enhances gemcitabine-induced cytotoxicity in vitro (Duxbury et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…It has been shown that an increase in RRM2 protein levels and RR activity in human nasopharyngeal cancer cells results in ionizing radiation resistance, which appears mediated by enhanced ionizing radiation damage repair during G2 phase of the cell cycle. However, overexpression of the large subunit, RRM1, of RR in these cells did not affect RR activity or ionizing radiation response (Kuo et al, 2003). RRM2 overexpression is also associated with gemcitabine chemoresistance in pancreatic adenocarcinoma cells, and that suppression of RRM2 expression using RNA interference enhances gemcitabine-induced cytotoxicity in vitro (Duxbury et al, 2004).…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, Triapine is a considerably more potent RR inhibitor and is effective against hydroxyurea-resistant murine and human tumor cells (18,21). Moreover, Triapine is equally effective against the hRRM2 and p53R2 components of the R2 subunit of RR (11), and it is the R2 subunit that has been shown to protect against radiationinduced cell death (4). Triapine has undergone phase I clinical trials and has been shown to have a favorable pharmacokinetic and toxicity profile (22 -26).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to radiosensitivity, Kuo et al (4) showed that whereas the overexpression of the R1 subunit has no effect on radiosensitivity, overexpression of the R2 subunit (in the form of hRRM2) protects against radiation-induced cell death, consistent with the R2 subunit of RR serving as a potential target for radiosensitization. Although a number of agents have been developed as RR inhibitors, hydroxyurea has received the most attention in preclinical and clinical studies.…”
mentioning
confidence: 99%
“…As maximal DNA synthesis requires high concentrations of dNTPs, the RNR activity plays an important role in cell proliferation (31). On the other hand, increased RNR activity has been associated with malignant transformation and resistance to chemotherapy (12,14,25,56).The class I RNR holoenzymes are commonly found in eukaryotes and eubacteria and comprise two subunits, R1 and R2 (34). The active site and multiple binding sites for allosteric effectors reside in R1 (20), which can exist as a dimer, tetramer, and hexamer depending on the nucleotides present and their concentrations (21,37,47).…”
mentioning
confidence: 99%
“…As maximal DNA synthesis requires high concentrations of dNTPs, the RNR activity plays an important role in cell proliferation (31). On the other hand, increased RNR activity has been associated with malignant transformation and resistance to chemotherapy (12,14,25,56).…”
mentioning
confidence: 99%